Study of Influence of Different Plantation Schemes for Pumpkin Growing on Productivity (In the Conditions of Khorazm Region) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, we will study how to plant pumpkin in local conditions in different planting schemes and varieties of Ispanskaya 73, pumpkin Tyoshchin pie, pumpkin Yaponskaya. Phenological observations were made during the vegetation period of pumpkin variety samples planted in different planting schemes. (2022-2023) Experimental selection of optimal planting scheme for Ispanskaya 73, pumpkin Tyoshchin pie, pumpkin Yaponskaya varieties.